Monitoring of land use and land cover changes in Mt. Pulag National Park using Landsat and sentinel imageries - Doyog, Nova D.; Lumbres, Roscinto Ian C.; Baoanan, Zenaida G. (Vol.150, No.4 (August 2021) pages 723-734.)
"The degree of land use and land cover (LULC) conversion of Mt. Pulag National Park (MPNP), Benguet Province, Philippines from 1990-2020 was assessed to provide valuable information for land resource management strategies. The increasing demand for vegetable farming threatens the park with further degradation. The magnitude of changes in the LULC of MPNP was determined using Landsat 5 for 1990-2010 and Sentinel-2 for 2020. The FLAASH (Fast Line-of-sight Atmosphere Analysis of Hypercubes) algorithm was performed to enhance the reflectance of the satellite images before data analysis"-Title page.